Gambaran Profil Psikologis Psychopathy Symptoms pada Tahanan Wanita Kasus Korupsi di Lapas Wanita Kelas IIA Sukamiskin Bandung - Medwin Wisnu Prabowo (MANASA, 2021)
There are many crimes that happened in this era, which one of them is corruption. Corruption has become a major phenomenon for each country in this world. Even more, it is not only male who doing the corruption, but female also. They were get some money to satisfy themselves although they have to break the law. This phenomenon has attracted researcher to study the female inmates who was doing corruption, and its relation to psychopathic symptom. Three female inmates in Sukamiskin Penitentiary Institute Class IIA – Bandung, who were convicted based on corruption cases, were chosen as subjects of this study. The result showed that all of three female inmates have a tendency to become a Psychopath, but in the low level to middle level tendencies. The three dominant Psychopathic Symptoms that found: pathological lying, lack of remorse or guilt, and short-term marital relationships. It can be summarized and recommended that among 3 subjects need to receive a counseling and/or psychoeducation so they will be more honest in their work setting, and to educate them that its important to have a good relationship to build a harmonious family.